2021
DOI: 10.3390/medicina57050469
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and Perinatal Outcomes after Very Early Preterm Premature Rupture of Membranes (PPROM)-A Retrospective Analysis over the Period 2000–2020

Abstract: Background and Objectives: Pre-term premature rupture of membranes (PPROM) responds for one third of preterm births, and it is associated with other complications that increase the risk of maternal or fetal poor outcome. To reduce uncertainty and provide accurate information to patients, the analysis of the large series is of great importance. In order to learn about the evolution over the time of the obstetric and perinatal outcomes in cases of PPROM at, or before, 28 weeks (very early PPROM) managed with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Given that gestational diabetes poses an additive impact on the risk of adverse pregnancy or delivery outcomes, we included gestational diabetes as a covariate [ 31 ]. We also, respectively, adjusted the other confounders (including PPROM, anemia, and preeclampsia) to eliminate the potential bias when addressing the pregnancy outcomes [ 27 29 ]. The results were consistent with the previous analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that gestational diabetes poses an additive impact on the risk of adverse pregnancy or delivery outcomes, we included gestational diabetes as a covariate [ 31 ]. We also, respectively, adjusted the other confounders (including PPROM, anemia, and preeclampsia) to eliminate the potential bias when addressing the pregnancy outcomes [ 27 29 ]. The results were consistent with the previous analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we included gestational diabetes as a covariate due to the fact that gestational diabetes possesses an additive impact on the risk of adverse pregnancy or delivery outcomes [ 26 ]. Also, other confounders (including PPROM, anemia, and preeclampsia) were, respectively, adjusted to eliminate the potential bias when addressing the pregnancy outcomes [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study showed that pregnancy duration after PROM was around 14 days, and latency increased over the years. With 53% of caesarean deliveries, the mortality rate was around 26.5% and decreased over the analyzed period ( p < 0.05) [ 26 ].…”
Section: Clinical Issuesmentioning
confidence: 99%
“…PPROM is linked to 30–50% of preterm births, as about 50–60% of women with PPROM remote from the term will deliver within one week even with conservative management ( Lyons and McLaughlin, 2020 ; Mercer, 2003 ). PROM can significantly increase morbidity and mortality of both mothers and infants ( Gonzalez-Mesa et al, 2021 ; Henderson et al, 2012 ; Mercer, 2003 ; Newman et al, 2009 ; Stan et al, 2013 ) and result in long-term neurodevelopment and mental health problems of infants ( Clark and Varner, 2011 ; Patkai et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%